Registration Legality of Deed of Establishment of Limited Partnership from District Court to Ministry of Law and Human Rights - Dewi Kartika; Ida Nadirah; Ramlan Ramlan (RIRAI Publisher, 2021)
Based on Article 23 of the KUHD, registration of the deed of establishment of Limited Partnership (CV) is carried out at the secretariat of the district court where the CV is established. However, since the enactment of the Regulation of Ministry of Law and Human Rights (Permenkumham) No.17/2018, registration of the deed of establishment Limited has been carried out through SABU which is under the auspices of the Directorate General of General Legal Administration, Ministry of Law and Human Rights. The position of Permenkumham No.17/2018 in the hierarchy of legislation in Indonesia is under the KUHD, so the purpose of this study was to determine the legality of the registration deed of CV from the district court to the ministry of law and human rights. This research uses normative research, with a statutory approach method and the level of legal synchronization, with qualitative analysis. Based on Article I of the Transitional Rules of the 1945 Constitution, the position of the KUHD is still a law, this is emphasized in Article 7 Paragraph (1) of Law No.12 of 2011. So that based on the principle of lex superior derogat legi inferior, then the authorities to carry out and receive registration deed of incorporation CV is the clerk of the district court where CV is located